Meningkatkan Karakter Bernalar Kritis dengan Penerapan Model Problem Based Learning di Sekolah Dasar - Nur Defani; Supriyadi Supriyadi (STKIP Singkawang, 2025)
This study aims to determine the improvement of students’ critical reasoning character by applying the Problem Based Learning model. This study used a quantitative approach with a pre-experimental design of one group pretest-posttest type. The population of this study were 4th grade students of SDN Kendalpecabean Sidoarjo, totalling 23 students. The data collection technique used saturated sampling. The research instrument is a critical reasoning ability test which includes four indicators, namely obtaining and processing information, analysing information, reflecting on thinking, and making decisions. The normality test results showed that the pre-test and post-test data had a normally distributed distribution, and the homogeneity test showed that the data was homogeneous. The paired sample t-test test showed a significant difference between the pre-test and post-test scores, with α = 0,05 obtained a significance value of < 0,001 which means H0 is rejected and H1 is accepted. In addition, the N-Gain test results showed an increase in students’ critical reasoning skills in the medium category. The results of this study indicate that the Problem Based Learning model has a positive effect on improving the critical reasoning character of grade IV elementary school students in Mathematics.